Benefícios e dificuldades na adoção de um sistema de gestão da qualidade no Rio Grande do Norte - Silva Junior, Mauro Tomaz da (2013)
Taking competitive advantage or satisfy the client are the reasons why companies have been implementing a Quality Management System (QMS). It brings benefits such as the improvement in the processes, products and services; an enhancement in the image of the company (marketing) and satisfaction of the clients. As a whole, this paper aims to evaluate the results obtained from the implementation of the QMS in the certified companies in the ISO 9001 standard, contained in the database of INMETRO, of the Rio Grande do Norte State (RN). In order to achieve the goals, a bibliographical research about the theme quality management system was made and, subsequently a survey was made with the managers of the certified companies in RN, using the online questionnaire. Out of 27 companies that have the certificate in Rio Grande do Norte, 21 responded the data collection instrument. The data analysis was made through techniques of descriptive and multivariate statistics: cluster analysis. The research instrument used contained 20 questions that address the main theme of this dissertation. Using the cluster analysis, four groupings that possessed similarities concerning the survey answers were found. This analysis allowed us to conclude that the QMS boosts significant improvements in the organizations, such as: quality in the reputation of the company and sales increase. On the other hand, it allowed us to identify as main difficulties: the dissemination of the quality culture, lack of commitment of the whole organization and the resistance of the workers